2017
DOI: 10.1259/bjr.20160689
|View full text |Cite
|
Sign up to set email alerts
|

Big Data in radiation therapy: challenges and opportunities

Abstract: Data collected and generated by radiation oncology can be classified by the Volume, Variety, Velocity and Veracity (4Vs) of Big Data because they are spread across different care providers and not easily shared owing to patient privacy protection. The magnitude of the 4Vs is substantial in oncology, especially owing to imaging modalities and unclear data definitions. To create useful models ideally all data of all care providers are understood and learned from; however, this presents challenges in the guise of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…These changes were observed in well-nourished subjects, and the magnitude is consistent with clinical paradigms [72]. Especially in older patients, bed rest related to hospital stay results in a diminished ability to perform basic activities of daily life, like transfers and walking [73][74][75]. The loss of independent physical functioning is a common side effect of hospitalization and is also called hospitalization-associated disability [35].…”
Section: Postoperative Stressorssupporting
confidence: 57%
See 2 more Smart Citations
“…These changes were observed in well-nourished subjects, and the magnitude is consistent with clinical paradigms [72]. Especially in older patients, bed rest related to hospital stay results in a diminished ability to perform basic activities of daily life, like transfers and walking [73][74][75]. The loss of independent physical functioning is a common side effect of hospitalization and is also called hospitalization-associated disability [35].…”
Section: Postoperative Stressorssupporting
confidence: 57%
“…Second, the readiness for change and willingness to share data should be increased. Lustberg et al [73] reported that the barriers for technological innovations and data-sharing are not of technological or ethical nature; however, barriers might be a lack of resources, expertise, and willingness to share data of health care professionals and researchers [73]. The absence of willingness to share data results from an ego-centered belief; the feeling of competition between institutes and not allowing comparison of performances with each other [73].…”
Section: Technology: Data-managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Big data has characterized by four V's: volume, variety, velocity and veracity [3]. In radiation oncology, data can be categorized as "Big Data" because (a) the use of dataintensive imaging modalities (volume), (b) the imaging archives are growing rapidly (velocity), (c) there is an increasing amount of imaging and diagnostic modalities available (variety), and (d) interpretation and quality differs between care providers (veracity) [4]. The radiation oncologists are overwhelmed with scientific literature, rapidly evolving treatment techniques, and the exponentially increasing amount of clinical data [5].…”
Section: Big Datamentioning
confidence: 99%
“…Very often, those systems and / or data formats might not be interoperable between each other's. No matter, what the source of clinical data is, data fragmentation represents one of the biggest issues when dealing with clinical data in general [1]. Data fragmentation occurs when a collection of data in memory is broken up into many pieces that are not close together.…”
Section: Introductionmentioning
confidence: 99%